1977
DOI: 10.1111/j.1365-2222.1977.tb01442.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific IgE antibodies in nasal secretion from patients with allergic rhinitis and with negative or weakly positive RAST on the serum

Abstract: Summary Nasal secretions from eighteen patients with allergic rhinitis with a positive case history, intradermal test and nasal provocation test, but with negative or only weakly positive RAST (radioallergosorbent test) on the serum against a total of thirty‐five allergens, were studied. In the RAST an immunosorbent‐purified anti‐IgE with Dɛ2 specificity was used, which raised the detection limit. Nasal secretion was collected by washing the nasal mucosa with 0.9% and 18% NaCl solution respectively, and the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 12 publications
(5 reference statements)
1
16
0
1
Order By: Relevance
“…216–222 It is not uncommon for individuals with allergic rhinitis or chronic rhinosinusitis (CRS) to manifest antigen-specific IgE in nasal secretions or nasal tissue with no apparent specific IgE in the serum for the same antigen, and documented cases exist in which nasal antigen challenge responses are elicited in individuals that lack skin test sensitivity. 215, 217, 218, 220 A survey study found that 19% of patients with rhinitis and polyposis had specific IgE in the nose but not the serum. 223 More recent studies, that used time resolved fluorescence immunosorbent assays to determine the relative proportions of total and specific immunoglobulins in the airways and circulation, concluded that the majority of the total body aeroallergen-specific antibodies of the IgE and IgA isotypes are produced in the airways, and that systemic sensitization largely reflects spillover of immunoglobulins from the mucosal site of their production into the circulation.…”
Section: B-lymphocytes In Chronic Diseases Of the Upper Airwaymentioning
confidence: 99%
“…216–222 It is not uncommon for individuals with allergic rhinitis or chronic rhinosinusitis (CRS) to manifest antigen-specific IgE in nasal secretions or nasal tissue with no apparent specific IgE in the serum for the same antigen, and documented cases exist in which nasal antigen challenge responses are elicited in individuals that lack skin test sensitivity. 215, 217, 218, 220 A survey study found that 19% of patients with rhinitis and polyposis had specific IgE in the nose but not the serum. 223 More recent studies, that used time resolved fluorescence immunosorbent assays to determine the relative proportions of total and specific immunoglobulins in the airways and circulation, concluded that the majority of the total body aeroallergen-specific antibodies of the IgE and IgA isotypes are produced in the airways, and that systemic sensitization largely reflects spillover of immunoglobulins from the mucosal site of their production into the circulation.…”
Section: B-lymphocytes In Chronic Diseases Of the Upper Airwaymentioning
confidence: 99%
“…Es ist demnach möglich, dass bei nasaler Allergie weder an der Haut noch im Serum spezifisches IgE nachweisbar ist. Der Nachweis einer Allergie gelingt in diesen seltenen Fällen nur durch nasalen Provokationstest an der Nasenschleimhaut selbst [25].…”
Section: Hintergrundunclassified
“…The first recognitions that IgE may be present exclusively in the nasal mucosa date back to the 1970s [9,10] and this phenomenon was occasionally reconsidered [11-14]. In 2003 the term “entopy” was proposed to differentiate local IgE production from atopy [13] but the recent definition by Rondon et al as local allergic rhinitis (LAR) seems more convincing [15].…”
Section: Introductionmentioning
confidence: 99%